Peran Dinas Sosial Dalam Penyaluran Program Sembako Di Kabupaten Sukabumi - Siti Nuraeni; Ike Rachmawati; Tuah Nur (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
Basic food program is a program which has released by the government to tackle poverty. But in implementation of basic food program there are still some problem, such as: 1) less careful from fasilitator in inputing data; 2) less socialization about basic food program to KPM; 3) quality of food is not suitable; and 4) there are not some recapitulation data about empty balace which has experienced by KPM. The purpose of this research is to know the role of social service in distributing basic food program in the Sukabumi District. In this research the writer used qualitative descriptive research. And snow ball sampling technique is used to determine informant. While in this research the writer used observation, interview, and documentation technique to collect the data. Role theory is used in this research by Jim Ife anda Frank Tesoriero (2016). The result of this research shows that the role of social service in distributing basic food program in Sukabumi District has been carried out well when viewed from the facilitating representation and technique role. But in the role of educating, it has not been maximized. This can be seen from the lack of information obtained by the public and KPM.